UPAYA KEPOLISIAN DALAM PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA JUDI ONLINE (STUDI KASUS DI POLRES BULELENG) - Kadek Setiawan; I Wayan Landrawan; Ketut Sudiatmaka (Jurnal Ilmu Hukum Sui Generis, 2023)
The crime of online gambling is an act that violates the law which is included in a crime and has become a habit for the community, including the City of Buleleng. Online gambling is a form of abuse of online media facilities where betting is used by transferring cash through banks, like gambling in general. If allowed to continue without serious handling from police law enforcement, people who carry out online gambling will become addicted and will have a negative impact on themselves and others. This study aims to analyze 1) the efforts made by the police to enforce the law against online gambling criminals in the Buleleng district. 2) Obstacles that hinder law enforcement efforts against perpetrators of online gambling crimes in the Buleleng district. This research uses an empirical juridical approach, the research is descriptive, the type of data is primary data and secondary data. Data collection techniques are observation, interviews and document studies. The sampling technique of non-probability sampling is in the form of purposive sampling and data analysis, namely qualitative analysis. The results of the study show that the efforts of the police in tackling online gambling crimes in the Buleleng City Police area are efforts made by the police in enforcing the law against online gambling crimes, penal efforts. The obstacles experienced by the Buleleng resort police in enforcing the law, are the difficulty of obtaining the suspect's address, the high mastery of the perpetrators in operating information technology.